Fyodor Mikhailovich Dostoevsky Today - Zabolotski, N. A. (Scottish journal of theology, 1984)
The centenary of the death of the Russian writer F. M. Dostoevsky (1821–81) is not merely an anniversary like any other, but a landmark in human history which deserves to be noted, observed and reflected upon. It is not just by chance that his novels and stories are still being read appreciatively, particularly by non-Russian speakers who have no background in Russian culture. Furthermore, it is not simply a desire to penetrate the secrets of the Russian heart, the peculiarities of the Russian character or the Russian style of life that creates their interest in his writings. Dostoevsky did of course reflect his own age and describe the situation in the Russia of his time, and it is valuable to study this aspect of his work. But it is not the whole. From the depth of his sensitive heart and with his prophetic finger this writer touched on something not exclusively Russian, but universal, global, even cosmic. He introduced philosophy and theology into a story in such a way that even a hundred years later everyone can find something familiar and personal in it, irrespective of his culture and language. He unearthed seeds which bore shoots many years later. He reflected in a Christian way on the crops and the future of what had been sown, and traced the mechanism of the historical process, not merely from the political and socio-economic point of view, but in human terms. This is probably the most significant feature of Dostoevsky's work.